Pengembangan Bahan Ajar Interaktif dengan Pendekatan Saintifik Bermuatan Nilai-nilai Karakter pada Materi Gelombang Bunyi, Gelombang Cahaya, dan Alat-Alat Optik di Kelas XI SMA/MA - Haflianita Hasanah; Murtiani Murtiani (PILLAR OF PHYSICS EDUCATION, 2018)
This research intends to produce interactive teaching materials that has been valid and practice tested. The teaching material presents matter of physic  with scientific approach contains character values in learning matter about sound wave, light wave, and optical devices. The teaching material is developed as a solution to increase student interest in physics. This research is a research and development (R&D) type that uses Plomp development model. Plomp development model has five phases, that is preliminary investigation phase, design phase, realization/construction phase, test, evaluation and revision phase, and implementation phase. But this research uses the phases only till the test, evaluation, and revision phase. For validity and practicality test this research uses questionnaire instruments. The validity questionnaire instrument is filled by three physics major of FMIPA UNP’s lecturers as the validators. For practicality questionnaire instrument is filled by two teachers and twenty students of SMAN 8 Padang as the practitioners. Finale data of the questionnaire instrument  is analyse by using Likert scale. From validity test, the developed interactive teaching material is rated very valid with percentage average score 86,4 %. From practicality test, the developed interactive teaching material is rated very practice by teachers and students with percentage average score by teachers 93 % and percentage average score by students 82,0 %. It means that the developed interactive teaching material is proper to be used in school as learning media.